1981
DOI: 10.1128/mcb.1.9.843
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate induction of collagen synthesis as a means for elucidating a mechanism of quantitative control of tissue-specific function.

Abstract: Ascorbic acid displays the characteristics of an ideal inducer of tissue-specific function in primary avian tendon cells in culture. It is a highly specific, potent stimulator of collagen synthesis, it demonstrates slow reversible kinetics, and it has no effect on growth rate of the cultured cells. Kinetic analysis of ascorbate induction of collagen synthesis was used to determine the critical steps in this complex biosynthetic pathway. Full hydroxylation of the proline residues in collagen, although probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 37 publications
1
25
2
Order By: Relevance
“…In both the bone and cell cultures, however, ascorbate was required for normal proline hydroxylation. In a few instances, there was a specific increase in the relative rate of collagen production by ascorbate under well-defined culture conditions, and it has been suggested that this occurs independently of the role of ascorbate in hydroxylation (14,50). It is not clear whether this modulation of collagen production by ascorbate in cell culture systems occurs by the same mechanism operative in vivo.…”
Section: Resultsmentioning
confidence: 86%
“…In both the bone and cell cultures, however, ascorbate was required for normal proline hydroxylation. In a few instances, there was a specific increase in the relative rate of collagen production by ascorbate under well-defined culture conditions, and it has been suggested that this occurs independently of the role of ascorbate in hydroxylation (14,50). It is not clear whether this modulation of collagen production by ascorbate in cell culture systems occurs by the same mechanism operative in vivo.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, PAT cells at low cell density or in a medium deficient in ascorbate will produce only 12% procollagen (22,26). This shift has previously been shown to be specific to procollagen production; the rate of noncollagen protein synthesis is identical in induced and uninduced cells (26).…”
mentioning
confidence: 99%
“…In the presence of 0.3 mM a,a'-dipyridyl there was a specific two-to threefold decrease in procollagen production after 4 h, but this was unaccompanied by a drop in procollagen mRNA levels. Therefore, inhibitor studies give further support to the idea that primary action of ascorbate is to release a post-translational block.Primary avian tendon (PAT) cells at high cell density (>4 x 104 cells per cm2) and in the presence of ascorbate (50 p.g/ml) allocate half of their protein production to procollagen (22,26). On the other hand, PAT cells at low cell density or in a medium deficient in ascorbate will produce only 12% procollagen (22,26).…”
mentioning
confidence: 99%
See 2 more Smart Citations